Anatomical Variants of Portal Vein Branching in CECT Scan of Abdomen: A Descriptive Study - Karki, Subindra; Paudel, Ram Chandra; Bhandari, Anupam; Phuyal, Arun; Dahal, Mohit Raj (Journal of Lumbini Medical College, 2021)
Introduction: Various anatomical variants are encountered in portal venous system which are quite important while undergoing hepatobiliary surgeries and percutaneous radiological interventions. Contrast enhanced computed tomography (CECT) of the abdomen is considered a better imaging modality to identify these variations. Methods: A descriptive prospective study was conducted in 1000 individuals undergoing CECT of abdomen. Triple phase CECT scan of the abdomen was done and the portal vein anatomy was reconstructed and analyzed. Results: Normal branching pattern of the portal vein was seen in 786 (78.6%) patients. Variations were seen in rest of the 214 (21.40%) patients. The most common variant was trifurcation of the portal vein seen in 113 (11.3%) patients. Right posterior portal vein as the first branch of main portal portal vein was found in 72 (7.2%) patients. Right anterior portal vein arising from left portal vein was seen in 29 (2.9%). Sixty nine of the 567 males had trifurcation accounting for 12.1% incidence of this variation amongst males. Trifurcation was seen in 44 of the 433 females resulting in an incidence of 10.1%. Forty-four (7.7%) males and 28 (6.4%) females had right posterior portal vein as the first branch of main portal vein. Right anterior portal vein was noted to arise from the left portal vein in 20 (3.5%) males and nine (2.07%) females. Conclusion: The most common variation in portal venous system was trifurcation of portal vein followed by right posterior as first branch and right anterior branch arising from left portal vein respectively